Testicular tumor arising from an intra-abdominal undescended testis in a 1-year-old child: a case report and literature review - Xia, Qiongzhang; Kuang, Tongshuai; Lin, Xiaokun; Zhang, Hua (Frontiers in Pediatrics, 2023)
Objectives: Testicular tumors in the intra-abdominal undescended testis are rare in children, and their management remains challenging. This study aimed to investigate the diagnosis and treatment of testicular tumors arising from undescended intra-abdominal testes in children. Methods: In this study, we retrospectively analyzed the clinical records of a 1-year-old male patient admitted to pediatric surgery in March 2022 with a testicular tumor originating in the intra-abdominal undescended testis. Furthermore, medical literature published in English during the last three decades was systematically searched through the databases of Medline, PubMed, and Google Scholar. Results: The patient underwent laparoscopic orchiopexy and tumor excision. The operation was uneventful, and the patient recovered well without complications. An 8-month follow-up showed no recurrence of the teratoma after postoperative pathology. The literature search resulted in the retrieval of 16 non-duplicate articles, and 16 patients were included in this review. The cases included six cases of left cryptorchidism and 10 cases of right cryptorchidism, with an average age of 15.3 months. The largest transverse diameter of the tumors ranged from 1.8 to 12.5 cm, with an average tumor length of 6.7 cm. All patients underwent surgical treatment, including three cases of laparoscopic exploration, one conversion of the inguinal incision to laparotomy, and 12 cases of laparotomy. Postoperative pathology revealed 12 cases of mature teratoma, two cases of immature teratoma, one case of yolk sac tumor, and a single case of embryonic carcinoma combined with yolk sac tumor. We followed up on nine cases, and none of them recurred. Conclusion: Preoperative Imaging examinations should be routinely performed prior to surgery to rule out possible intra-abdominal testicular tumors, particularly in cases of non-palpable undescended testis. Early diagnosis and prompt surgical intervention resulted in an excellent outcome.